FORMATION OF STUDENTS 'READINESS FOR LOCAL HISTORY WORK IN THE SYSTEM OF PERSONALLY ORIENTED HIGHER EDUCATION PEDAGOGICAL SCHOOL - O.V. Bondarenko (Academy of Cognitive and Natural Sciences, 2003)
No abstract.